Combinatorial phenethyl isothiocyanate and withaferin A targets multiple epigenetics pathways to inhibit MCF-7 and MDA-MB-231 human breast cancer cells - Mohammad Mijanur Rahman; Trygve O. Tollefsbol (Cancer Cell International)
Abstract Background Epigenetic phytochemicals are considered as an efficacious and safe alternative to synthetic drugs in drug discovery. In this regard, combinatorial interventions enable simultaneously targeting various neoplastic pathways to eradicate multiple tumorigenic clones. Therefore, we evaluated the effects of the epigenetic-modifying compounds phenethyl isothiocyanate (PEITC) and withaferin A (WA) alone and in combination on cancer hallmarks and miRNome profiles of breast cancer (BC) cells in addition to their impact on multiple epigenetic regulatory pathways. Methods We performed MTT assay, flow cytometry-based cell cycle analysis, apoptosis assay, stem cell population analysis, and mammosphere assay on MCF-7 and MDA-MB-231 BC cells to evaluate the effect of combinatorial PEITC and WA treatment on cancer hallmarks. To assess the epigenetic effects of the combinatorial PEITC and WA treatment, we conducted HDAC activity assay, DNMT activity assay, western blot analysis, siRNA-mediated gene knockdown, and RT-qPCR analysis. Additionally, we explored the effect of the PEITC + WA combination on miRNome profiles in MCF-7 and MDA-MB-231 BC cells through miRNA-seq analysis and miRNA Real-Time PCR assay. Results Our results indicated a synergistic effect of PEITC and WA on inhibiting MCF-7 and MDA-MB-231 BC cells by triggering G2/M-phase arrest, apoptosis induction, tumor formation efficiency decrease, and stem cell population decline. Combinatorial PEITC and WA treatment significantly reduced global DNA methyltransferase (DNMT) and histone deacetylase (HDAC) activity in addition to decreasing multiple Class I HDACs and de novo DNMTs expression in MCF-7 and MDA-MB-231 cells. PEITC + WA combination targets histone acetylation and DNA methylation pathways since the expressional changes of cell cycle and apoptosis-related proteins due to PEITC + WA treatment closely mimic the alterations seen when HDAC8 and DNMT3B are silenced. Furthermore, treating these cells with PEITC and WA significantly alters the expression of several BC-associated miRNAs. Conclusion Overall, our investigation demonstrated that combined PEITC and WA is effective in inhibiting MCF-7 and MDA-MB-231 BC cells by impacting multiple epigenetic regulatory pathways.